A nine-degree-of-freedom optimization-based method to evaluate the isocenter coincidence of the treatment beams and image system of a medical accelerator - Zhou, Yun; Qiao, Jian; Yan, Nan; Dai, Liyan; Pu, Yuehu (Frontiers in Physics, 2024)
Medical accelerators have been widely used in tumor radiation therapy. Accurate isocenter coincidence between treatment beams and imaging systems is critical for image-guided radiation therapy (IGRT). We propose a method utilizing a phantom with marker spheres to detect the Nine Degrees of Freedom (9-DOF) in the system's geometric model to assess isocenter coincidence between the treatment beams and the kV cone-beam computed tomography (CBCT). The phantom was initially aligned with the accelerator. Subsequently, the projections of the treatment and CBCT beams' were acquired separately with full gantry rotation. By analyzing the marker spheres' position in both the treatment beam and CBCT beam projections, the 9-DOF parameters were calculated. A comparison with a Winston-Lutz-based system was performed. Then, the analysis revealed imprecise circular trajectories with noticeable random deviations in the rotations of both the treatment beams and CBCT. The isocenter deviations for the treatment beams and CBCT were 0.18 mm (X), -0.49 mm (Y), and -0.35 mm (Z) after trajectories fitting, respectively. The rotational planes of the two systems exhibited a pinch angle of 0.0235°. This proposed method offers a quantitative